Phosphoproteomics identifies microglial Siglec‐F inflammatory response during neurodegeneration - Nader Morshed; William T Ralvenius; Alexi Nott; L Ashley Watson; Felicia H Rodriguez; Leyla A Akay; Brian A Joughin; Ping‐Chieh Pao; Jay Penney; Lauren LaRocque; Diego Mastroeni; Li‐Huei Tsai; et al. (Molecular Systems Biology)
Abstract Alzheimer’s disease (AD) is characterized by the appearance of amyloid‐β plaques, neurofibrillary tangles, and inflammation in brain regions involved in memory. Using mass spectrometry, we have quantified the phosphoproteome of the CK‐p25, 5XFAD, and Tau P301S mouse models of neurodegeneration. We identified a shared response involving Siglec‐F which was upregulated on a subset of reactive microglia. The human paralog Siglec‐8 was also upregulated on microglia in AD. Siglec‐F and Siglec‐8 were upregulated following microglial activation with interferon gamma (IFNγ) in BV‐2 cell line and human stem cell‐derived microglia models. Siglec‐F overexpression activates an endocytic and pyroptotic inflammatory response in BV‐2 cells, dependent on its sialic acid substrates and immunoreceptor tyrosine‐based inhibition motif (ITIM) phosphorylation sites. Related human Siglecs induced a similar response in BV‐2 cells. Collectively, our results point to an important role for mouse Siglec‐F and human Siglec‐8 in regulating microglial activation during neurodegeneration.